200 keV Ar+ Induced Growth of Silver Nanoparticles in Soda Lime Glass. Issue 205 (12th February 2020) - Sonal,; Sharma, Annu; Aggarwal, Sanjeev
Abstract: Thin layer of silver nanoparticles was formed few layers below the soda lime glass surface using Na + ↔ Ag + ion-exchange method, followed by Ar + implantation at 30°. Confirmation of synthesis of silver nanoparticles and investigation of sample morphology were carried out using field emission scanning electron microscopy and glancing angle X-ray diffraction whereas UV-Visible spectroscopy was utilised for evaluation of various optical parameters like optical energy gap, Urbach's energy and optical conductivity. The data obtained through UV-Visible spectroscopy revealed that the optical energy gap decreased whereas Urbach's energy and optical conductivity increased with the synthesis of silver nanoparticles in glass matrix.